Paraboremia selaginellae enhances Salvia miltiorrhiza growth and cadmium tolerance via modulating root architecture and cadmium speciation in contaminated environments - Lin, Yuli; Wang, Zhenzhou; Chen, Wenjing; Liu, Yunfeng; Li, Xia; Tang, Hongliang; He, Xueli (Frontiers in Plant Science, 2025)
IntroductionDark septate endophytes (DSEs) commonly colonize plant roots in heavy metal-polluted habitats, but little is known about the potential mechanisms driving medicinal plants to adapt to heavy metal-polluted environments. Here, we investigated the growth of Paraboeremia selaginellae strains and their enhancing of cadmium (Cd) tolerance and growth in Salvia miltiorrhiza in Cd-contaminated soil.MethodsFirst, we tested the Cd resistance of P. selaginellae by in vitro culture. Then, we studied the performance of S. miltiorrhiza inoculated with P. selaginellae in Cd-contaminated soil.ResultsIt was found that P. selaginellae possessed a capacity to accumulate Cd in its mycelium. The Cd-contaminated environment increased the content of melanin and osmotic substances and reduced the proportion of the highly toxic chemical form of Cd in the mycelium of P. selaginellae. In Cd-contaminated soil, P. selaginellae effectively colonized plant roots and improved soil nutrients and the growth of S. miltiorrhiza. The P. selaginellae-inoculated treatment significantly increased the contents of effective nitrogen (37.74%), urease (31.55%), and alkaline phosphatase (29.82%) in 10 mg Cd/kg soil, compared with the non-inoculated treatment. More importantly, P. selaginellae inoculation increased root biomass for 5 and 10 mg Cd/kg soil by 42.35% and 30.21%, respectively, in comparison to non-inoculated control. Inoculation with P. selaginellae reduced the proportion of the highly toxic chemical form of soil Cd, and reduced the accumulation of Cd in plants, especially in the roots.DiscussionThese results indicated that DSEs have a positive influence on the growth and Cd tolerance of S. miltiorrhiza, and reduce the biological toxicity of soil Cd. Therefore, exploitation and utilization of DSEs resources might be a new method for improving the cultivation of medicinal plants and soil microenvironment in heavy metal-contaminated areas.